Remote sensing monitoring of mountain sustainable development goals (SDG15.4): a systematic review - Jinhu Bian; Jinping Zhao; Ainong Li (International Journal of Digital Earth)
Mountains are widely acknowledged as essential components of terrestrial landscapes. However, mountain ecosystems are particularly sensitive to climate and environmental changes. The sustainable management of the natural resources and ecological services provided by mountain systems is imperative. The 2030 agenda for sustainable development specifically established Sustainable Development Goal (SDG 15.4) to protect and promote the sustainability of mountain ecosystems. Researchers and policymakers have widely endorsed the use of remote sensing (RS) to monitor and evaluate progress in achieving mountain sustainable development. This paper firstly reviewed the mountain sustainable development from a conceptual framework to a defined objective process. A total of 804 publications since 2000 were retrieved using keyword searches. Based on bibliometric analysis, this study explores the various methods and resources used for monitoring SDG 15.4. RS monitoring methods on monitoring and assessment of mountain SDG indicators were introduced in detail. This review also discussed the challenges of using RS to monitor mountain SDG indicators, the limitations of SDG 15.4, and its interactions with other SDG targets. Halfway through the SDGs deadline, this study is helpful to review the research progress of mountain SDG indicators and provide support for promoting the realization of mountain SDG in 2030.